An Examination of Substitute Heirs in Islamic Civil Law in Indonesia: An Interpretative Analysis of Legal Verses - Suarni, Suarni; Syukrinur, Syukrinur (Hukum Keluarga Islam IAIN LANGSA, 2024)
In Islamic inheritance law, inheritance occurs because of the relationship between sababiyah and nasabiyah. From these two relationships, the dzawil faraid', 'Asabah and dzawil Arham groups were born. Dzawil Arham is a group that is often overlooked in inheritance, because there are no absolute provisions, especially for grandchildren whose parents died before their grandfather or successor heir. Even though there is inheritance law to realize justice and benefit in the family. Thus, in this study we will examine in more depth related to replacement heirs from the perspective of the Al-Qur'an, with the aim of realizing replacement heirs in the Al-Qur'an. The method used by liberal research is an analytical descriptive approach. The results of this study are that basically in Islamic inheritance law the term substitute heir is not found in the Koran as a source of Islamic law. However, Hazairin through his ijtihad interpreted the lafaz mawali in the Qur'an 4:7 as a substitute heir. This meaning was then formulated in KHI article 185 paragraphs 1 and 2. As a contribution to this study, realizing justice and benefit is a necessity. Grandchildren as substitute heirs for their parents should be a provision in Islamic inheritance.